PENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS III SD MELALUI PERMAINAN LOMPAT KELINCI - Antonia Mantolas; Aleksander Lakapu (Asimtot : Jurnal Kependidikan Matematika, 2019)
The aim of this clas’s action research was intended to increase the numeracy skills of student 3rd grade through to game of rabbit jumping. This research was focus on the 3rd grade of SD GMIT Niki-Niki in the 2018/2019 school year. The analysis on the data which collected through test and interviews showed that the numeracy skills of student 3rd grade improved through the game of rabbit jumping.